2017
DOI: 10.1590/1678-4324-2017160433
|View full text |Cite|
|
Sign up to set email alerts
|

Anticandidal effect of endophytic bacteria isolated from Equisetum arvense L. against Candida albicans and Candida glabrata

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…They concluded that E. arvense could be a valuable source for natural anti-candidate agents. 37 The results of a study by de Oliveira et al about the effects of E. arvense and P. granatum peel extracts on C. albicans biofilm were also quite consistent with the results of the inoculation study. 38 In a study, Menezes et al evaluated the efficacy of hydroalcoholic Pomegranate extract on orthodontic dental plaques in 60 patients and compared to CHX as a standard.…”
Section: Discussionsupporting
confidence: 75%
“…They concluded that E. arvense could be a valuable source for natural anti-candidate agents. 37 The results of a study by de Oliveira et al about the effects of E. arvense and P. granatum peel extracts on C. albicans biofilm were also quite consistent with the results of the inoculation study. 38 In a study, Menezes et al evaluated the efficacy of hydroalcoholic Pomegranate extract on orthodontic dental plaques in 60 patients and compared to CHX as a standard.…”
Section: Discussionsupporting
confidence: 75%
“…Psychrobacillus soli could degrade around 72% of oil components at an initial oil concentration of 1500 ppm [ 35 ]. Among ten endophytic bacteria, Psychrobacillus insolitus and Curtobacterium oceanosedimentum showed the highest anticandidal effect against Candida albicans and C. glabrata [ 36 ], while two strains of P. insolitus (Mam2 and Ame3) exhibited an inhibitory action against staphylococcal strains isolated from food [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…None of the previous studies explicitly targeted the documentation of the bacteria communities colonizing the leaf endosphere using a high throughput sequencing approach. Instead, several studies employed the more traditional approach to cultivate bacteria to discover strains with antimicrobial activities ( Das et al, 2017a , b , c , 2018 ), or to document the variation used by growth regimes ( de Araújo-Barros et al, 2010 ). 16S rRNA sequences were utilized in several studies, but these studies were designed to address particular research foci such as the discovery of chloromethane degraders ( Jaeger et al, 2018 ; Kroeber et al, 2021 ) or heavy-metal resistant strains ( Zhu et al, 2014 ; Xu et al, 2016 ; Gu et al, 2018 ; Antenozio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, the best-studied microbiomes of ferns are associated with the water fern Azolla filiculloides ( Dijkhuzien et al, 2017 ; Banach et al, 2020 ), the arsenic hyperaccumulator Pteris vittata ( Zhu et al, 2014 ; Xu et al, 2016 ; Gu et al, 2018 ; Yang et al, 2020 ; Antenozio et al, 2021 ), and the xeric fern Pellaea calomelanos ( Mahlangu and Serepa-Dlamini, 2018a , b ; Tshishonga and Serepa-Dlamini, 2019 , 2020 ; Diale et al, 2021 ). The later studies explicitly focused on the genomes of cultivated endophytic bacteria, whereas other studies explored specifically antibacterial properties ( Das et al, 2017a , b , c , 2018 ), growth-promoting abilities ( Mukherjee et al, 2017 ; Rakshit and Sukul, 2021a , b ), and ecological aspects in general ( Jackson et al, 2006 ; de Araújo-Barros et al, 2010 ; Li F. et al, 2019 ). Enhancing our understanding of the endophytic bacterial communities are expected to specify the evolutionary history of the origin of the bacterial proteins such as Tma12 recovered in some fern genomes ferns arguably as a consequence of horizontal gene transfer ( Li F. W. et al, 2019 ; Yadav et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%